Building Entrepreneurial Capabilities through Co-Creation Multiformat Branding and Omnichannel Marketing - Denny Rakhmad Widi Ashari; Sawal Sartono; Bondan Subagyo; Gautama Sastra Waskita; Eko Santoso (ADI Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) face increasing challenges in improving their competitiveness in the digital economy, particularly in marketing communication, brand consistency, and digital platform utilization. This community engagement program aimed to strengthen MSMEs’ entrepreneurial and digital marketing capabilities through training in copywriting, multi-format content branding, and omnichannel marketing strategies. The program was conducted at the Integrated Business Service Center (PLUT) of Tulungagung Regency and involved 30 MSMEs supported by Bank Negara Indonesia (BNI) and PLUT from the culinary, coffee, creative industry, service, and retail sectors. The methods included needs assessment, training based on the AIDA (Attention, Interest, Desire, Action), PAS (Problem, Agitate, Solution), dan FAB (Features, Advantages, Benefits). Data were collected through participant observation, documentation, participant-generated outputs, and feedback. The results demonstrated improved understanding of brand identity, persuasive communication, and omnichannel marketing. Participants successfully developed promotional content, marketplace product descriptions, and practical branding plans that could be directly implemented in their businesses. The program effectively enhanced MSMEs’ digital readiness, entrepreneurial capacity, and long term competitiveness in the digital economy